HBED-NN: a bifunctional chelator for constructing radiopharmaceuticals - Makarem, Ata; Klika, Karel D.; Litau, German; Remde, Yvonne; Kopka, Klaus (The journal of organic chemistry, 2019)
Radiometal-based radiopharmaceuticals bearing bifunctional HBED chelators are powerful radiotracers for cancer diagnosis and therapy. Bifunctional HBED chelators make strong complexes with trivalent gallium and are able to bind to bioactive molecules through covalent bonds. However, thus far, no bifunctional HBED chelator capable of direct conjugation via click chemistry has been reported. We hereby introduce HBED-NN as a structurally new bifunctional HBED chelator for direct click coupling. We also investigated the complex chemistry of [Ga-(HBED-NN)] for potential use in gallium-based radiopharmaceuticals.